Measuring business performance in the airport context: a critical review of literature. Issue 8 (14th November 2016) - Fasone, Vincenzo; Zapata-Aguirre, Sandra
Abstract : Purpose: Over 15 years have passed since the first paper was published applying data envelopment analysis (DEA) to measure airport productivity. Since then, a wave of studies has appeared refining and validating this technique as one of the most reliable in the airport context. The purpose of this paper is to conduct a critical review of this accumulated literature. Design/methodology/approach: This paper presents an exhaustive review of approximately 60 peer-reviewed published papers on business performance measurement through DEA applications in the airport industry. Findings: The paper analyses the research on DEA technique chronologically and by geography. Managerial and academic practitioners' interest in conducting performance measurement studies has grown and benchmarking techniques have become more sophisticated. Research limitations/implications: Despite the popularity of the methodological framework of DEA, it can be improved by further research to continue refining and exploiting deeply the basic DEA scores. Some innovations have appeared from studies using alternative approaches to DEA, e.g. a Bayesian approach. Practical implications: The conclusions explore the research contribution, its final value delivered to airport management and some practical aspects and recommendations for the selected field of work. Originality/value: The paper explores the contribution of research to final value delivered to airport management by describing the main complementary procedures refining DEA technique scores for improving the operational efficiencies of airports through benchmarking. As well as by presenting the results of the assessment of major determinants of efficiency at airports around the world.